K27-Linked Diubiquitin Inhibits UCHL3 via an Unusual Kinetic Trap. Issue 2 (18th February 2021) - van Tilburg, Gabriëlle B.A.; Murachelli, Andrea G.; Fish, Alexander; van der Heden van Noort, Gerbrand J.; Ovaa, Huib; Sixma, Titia K.
Summary: Functional analysis of lysine 27-linked ubiquitin chains ( K27 Ub) is difficult due to the inability to make them through enzymatic methods and due to a lack of model tools and substrates. Here we generate a series of ubiquitin (Ub) tools to study how the deubiquitinase UCHL3 responds to K27 Ub chains in comparison to lysine 63-linked chains and mono-Ub. From a crystal structure of a complex between UCHL3 and synthetic K27 Ub2, we unexpectedly discover that free K27 Ub2 and K27 Ub2 -conjugated substrates are natural inhibitors of UCHL3. Using our Ub tools to profile UCHL3's activity, we generate a quantitative kinetic model of the inhibitory mechanism and we find that K27 Ub2 can inhibit UCHL3 covalently, by binding to its catalytic cysteine, and allosterically, by locking its catalytic loop tightly in place. Based on this inhibition mechanism, we propose that UCHL3 and K27 Ub chains likely sense and regulate each other in cells. Graphical Abstract: Highlights: UCHL3 binds preferentially to Lys27-linked diubiquitin ( K27 Ub2 ) over other Lys linkages UCHL3 is strongly inhibited by free K27 Ub2 and by K27 Ub2 -linked substrates K27 Ub2 inhibits UCHL3 covalently and allosterically by a stochastic mechanism This inhibition suggests that UCHL3 and K27 Ub2 are a stimulus-sensor pair in cells Abstract : Van Tilburg, Murachelli, et al. report how UCHL3, a deubiquitinase, is specifically inhibited by Lys27-linked diubiquitinated substrates. The inhibition is covalent and allosteric and relies on an unusual stochastic mechanism. The mode of inhibition suggests that UCHL3 and K27 Ub2 might be a stimulus-sensor pair in the cell.